Effects of Stock Market Development on Economic Growth in Nepal - Baral, Krishna Babu (Janapriya Journal of Interdisciplinary Studies, 2019)
Financial intermediaries and stock markets are important for the economic growth. The relationship between stock market development and economic growth has been extensively studied in the recent years. This study used analytical research design that involves bi-variate analysis by using simple regression model to examine the relationship between stock market development (measured by size and liquidity of the stock market) and economic growth (measured by logarithm of capital GDP at constant price) in Nepal during the period 2007-2017. Secondary data were collected from the official websites of Ministry of Finance (MoF) and Nepal Stock Exchange (NEPSE). It is assumed that economic growth is the function of stock market development for the purpose of data analysis. Empirical results of this study indicate significant positive relationship between economic growth and stock market development. Moreover, stock market development explained considerable variations in economic growth of Nepal i.e. size of the stock market explained 57.7 percent, and liquidity of the stock market explained 41.6 percent variation in economic growth of Nepal.